2021
DOI: 10.1016/j.scitotenv.2021.145768
|View full text |Cite
|
Sign up to set email alerts
|

Bumpy structured nanofibrous membrane as a highly efficient air filter with antibacterial and antiviral property

Abstract: Recently, the pandemic infectious diseases caused by coronavirus have prompted the development of air filter membranes to against infectious agents and protect human health. This research focuses on air filter membrane with antibacterial and antiviral property for high-efficiency particulate matter (PM) removal. Herein, polyamide-6 electrospun nanofibers were anchored with silver nanoparticles through hydrogen-bond. Bumpy nanorough surface and multilevel structure contribute to improve capture capacity, and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 46 publications
(37 reference statements)
0
34
0
Order By: Relevance
“…Studies have shown that several ways of transmission for SARS-CoV-2 include droplet transmission, body fluid transmission, aerosol transmission, and contact with contaminated surfaces [4,5]. In addition, microorganisms such as bacteria and viruses in the air can attach to particulates, which gradually enter the human organs through the respiratory system, leading to cardiovascular and respiratory diseases [6,7]. Accordingly, in addition to using diagnostic tools to screen infected people and isolate them to prevent further spread of the virus, people are encouraged to wear suitable protective equipment, such as an N95 face mask, which has proved to be the most effective infection control approach [8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that several ways of transmission for SARS-CoV-2 include droplet transmission, body fluid transmission, aerosol transmission, and contact with contaminated surfaces [4,5]. In addition, microorganisms such as bacteria and viruses in the air can attach to particulates, which gradually enter the human organs through the respiratory system, leading to cardiovascular and respiratory diseases [6,7]. Accordingly, in addition to using diagnostic tools to screen infected people and isolate them to prevent further spread of the virus, people are encouraged to wear suitable protective equipment, such as an N95 face mask, which has proved to be the most effective infection control approach [8].…”
Section: Introductionmentioning
confidence: 99%
“…Ag nanoparticles were loaded on PA6/PP membrane by immersion method. Their results demonstrate this membrane exhibits high PM2.5 filtration efficiency of 99.99% and low pressure drop of 31 Pa; simultaneous removal of multiple aerosol pollutants, e.g., SO x , NO x , methylbenzene, L-Nicotine; superior antibacterial performance against Escherichia coli (Gram negative bacteria) and Staphylococcus aureus (Gram positive bacteria), antiviral property against Porcine Delta coronavirus and not significant cytotoxicity [ 119 ].…”
Section: Tissue Engineeringmentioning
confidence: 99%
“… Schematics showing PA6@Ag ENM as an air filter membrane with antibacterial and antiviral property [ 119 ]. …”
Section: Tissue Engineeringmentioning
confidence: 99%
“…The results show that the gradual release of Ag ions from the membrane was effective in deactivating viruses and enhancing a long-lasting antiviral property. Ju et al [ 61 ] synthesized a nanofibrous air filter membrane for high-efficient particulate matter (PM) removal and antiviral and antibacterial properties. The membrane was fabricated by anchoring AgNMs to the polyamide through hydrogen bonding.…”
Section: Antiviral Nanomaterialsmentioning
confidence: 99%